AUTOMATED RESTAURANT SERVICE MANAGEMENT SYSTEM - Kalpesh V. Joshi; Akshay P. Dhawale; Chinmay Y. Dhekane (International Journal of Innovations in Engineering Research and Technology, 2021)
Today, in the era of rapid advancement in the technology, the world attempts to automate every possible task ensuring ease to human life with improved work-efficiency and quality [1]. This report describes in detail the design, development and functionality of a Smart On-Floor Service Management System developed exclusively for restaurants. The system comprises of an online wireless module enabling the customers to order food from the comfort of their respective tables via tablet phones; and a robot for delivering the dishes to the customers at their respective tables. The order once placed and confirmed by the customers will be directed to the kitchen on a LCDscreen. Once ready, the order will be delivered by the robots to their respective table. The project solely aims in aiding the restaurants with a practically implementable automated on-floor service management system.